Effects of Bracket Creep and Tax Reform on Average Personal Income Tax Burden in Germany - Chang Woon Nam; Christoph Zeiner (Center for Economic Studies and ifo Institute (CESifo), 2015)
This study aims at contributing to the ongoing debates on the bracket creep, whether Germany needs an integration of inflation indexation into its personal income tax system in order to re-duce distortions of tax liabilities and additional tax burdens. On the other hand, Germany has continuously flattened the personal income tax rates in the context of a series of tax reforms and modified its tax system. Under the consideration of the major goals of these reforms this study compares the extent to which the previous reform efforts, made in this country since 1958, have led to the change of the real, inflation-adjusted average personal income tax burden of the single earners in 2014. By doing so, it highlights that understanding the tax reform from a nominal point of view alone can fail to capture all the, also some `unexpected', real changes in average tax burden, when the `hidden' distortion caused by inflation prevails. According to the long-term real view adopted in this study, the evolution of German personal income tax system made the middle-income single earners worse-off, while the lower as well as the higher income groups are significantly better off.
Keywords: H21; H23; H24; H31; 330; personal income taxation; bracket creep; real average tax burden; single earners; coefficient of residual income progression; Germany